2013
DOI: 10.1063/1.4818325
|View full text |Cite
|
Sign up to set email alerts
|

Field to thermo-field to thermionic electron emission: A practical guide to evaluation and electron emission from arc cathodes

Abstract: This work is concerned with devising a method of evaluation of electron emission in the framework of the Murphy-Good theory, which would be as simple and computationally efficient as possible while being accurate in the full range of conditions of validity of the theory. The method relies on Pad e approximants. A comparative study of electron emission from cathodes of arcs in ambient gas and vacuum arcs is performed with the use of this method. Electron emission from cathodes of arcs in ambient gas is of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
0
14
0
4
Order By: Relevance
“…It was found that the simulation results are affected by the way in which the Murphy-Good formalism in the calculation of electron emission is implemented. The approach employed in this paper, as well as in [13], is based on the method in [26]. The latter relies on Padé approximants and is accurate in the whole range of validity of the Murphy-Good theory from field to thermo-field to thermionic emission, while being as simple and computationally efficient as possible.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…It was found that the simulation results are affected by the way in which the Murphy-Good formalism in the calculation of electron emission is implemented. The approach employed in this paper, as well as in [13], is based on the method in [26]. The latter relies on Padé approximants and is accurate in the whole range of validity of the Murphy-Good theory from field to thermo-field to thermionic emission, while being as simple and computationally efficient as possible.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Если же считать электронную эмиссию чисто термической, т. е. происходящей над потенциальным барьером, то нужно перейти к пределу h 0 → 0, что дает g(h 0 ) = 1 и I(h 0 ) = exp(s en /k b T ). В результате из (4) следует формула Ричардсона-Дэшмана, в которой учитывается снижение высоты потенциального барьера в электрическом поле (эффект Шоттки) [6,7,11], а соотношение (10) для эмиссионной эффективности пленки принимает вид:…”
Section: описание моделиunclassified
“…Для самосогласованного же нахождения характеристик разряда нужно дополнить эту систему уравнениями катодного слоя дугового разряда и уравнением теплопроводности в объеме катода [4,8,11,32,33].…”
Section: описание моделиunclassified
See 2 more Smart Citations